2012
DOI: 10.1021/ml200280r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and in Vitro Antileishmanial Evaluation of Chromene-2-thione Analogues

Abstract: Leishmaniases are an epidemic in various countries, and the parasite is developing resistance against available drugs. Thus, development of new drugs against Leishmania is an open area of investigation for synthetic organic chemists. To meet this challenge, a series of chromene-2-thione derivatives have been synthesized and docked into the active site of trypanothione reductase (TryR) enzyme required for redox balance of the parasite. These were screened on promastigote, axenic amastigote, and intracellular am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…This drug has shown minimal side effect with antileishmanial activity in animal model, when it was administered orally (Wyllie, Patterson, & Fairlamb, 2013;Wyllie et al, 2012). interactions (Hazra et al, 2013;Verma et al, 2012) (Sahoo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This drug has shown minimal side effect with antileishmanial activity in animal model, when it was administered orally (Wyllie, Patterson, & Fairlamb, 2013;Wyllie et al, 2012). interactions (Hazra et al, 2013;Verma et al, 2012) (Sahoo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The key purpose of our study is to predict interaction of the main binding sites of a ligand with a targeted enzyme of three-dimensional structure results in docking score (Venkatesan, Shukla, & Dubey, 2010;Verma et al, 2012). ADMET and QikProp studies were carried out to check toxicity associated with ligand and it was found that maximum number of 5-Nitroimidazole analogues have shown MRTD values above 3.4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the residues occupying the active site were Cys-52 and Cys-57 form chain-B. These residues are conserved and surrounded by aforementioned H-bond forming amino acid residues [18]. Ligand showing interaction with these two amino acid residues might change the active site structure leads to enzyme inhibition and ultimately parasite clearance.…”
Section: à2mentioning
confidence: 99%